Penetration depth consideration for better perforation performance - Samsuri, Ariffin (Faculty of Chemical & Natural Resources Engineering, 1992)
For optimum perforated well productivity, perforation must be deep enough to overcome any damage or barrier, cause minimum damage, clean, effective and stable. The importance of penetration depth to the perforated well productivity is determine by the completion type, gun, charge, formation rock properties, stress, gun clearance, casing and cement thickness. Generally, the productivity will be increased with increasing penetration depth but on the other hand, the perforation stability and/or the perforated wellbore stability decreases as the penetration depth increase, and deeper perforations are more difficult to clean.